Relation between Result and Size of Training Loads in 400-Metre Hurdle Race of Men - Jakub Adamczyk (Lithuanian Sports University, 2018)
Four-hundred-metre hurdle race is a very complex competition event, and besides classical motor abilities, such as speed, strength and endurance, the important components of it are rhythm, flexibility, coordination and jumping ability. The best competitors cover this distance in less than 50 seconds. The efforts of the hurdlers are connected with very high intensity work and with remarkable increase of acidity in working muscles, that is why four-hundred-metre hurdle race is thought to be one of the most difficult track and field competitions. Contemporary sport is characterized by the intense specialization, and thus training optimization is necessary. The aim of this research was to establish means of training which are essential to achieve high results in 400-metre hurdle race of men. The research included the data characterizing a one-year training cycle of 25 Polish high sport level 400 m hurdlers (average result 51.25 s). For the analysis TreOb 4.0 computer programme was used and the identified training means groups in 400-metre hurdle race (Iskra, 1995). For six groups of exercises, a positive relation with the sport results was found in all periods when they were applied. Exercises of racing power (including multi-jumps) over 40 metres were in this group as other exercises as Medium interval special endurance, Interval rhythm and Long rhythm endurance. Similar research performed by J. Iskra (2001) shows common elements which prove that some of the training means have influence on the sports results. In each of the stages, a high correlation was ascribed to the means developing special endurance. High correlation was characteristic of the race of sub-maximum intensity, rhythm long endurance (8 and more hurdles). Significant relation with the result was also found in the racing endurance. The results also demonstrate the significance and importance of the interval racing training means. Undoubtedly, analysing data we must have in mind the different reaction of competitors to applied training loads which are essential for high results in the 400-metre hurdle race. Such training prepares competitors for a high intensity work load under the conditions of increasing fatigue and muscle acidity. After taking the individualization of the training process into consideration, the data collected can become the model of training for 400 m H runners representing high sport level. Keywords: athletics, training loads, 400-metre hurdle race of men.